Advanced DC/AC inverters : applications in renewable energy - Luo, Fang Lin (Power electronics, electrical engineering, energy, and nanotechnology., 2013)
"Renewable energy systems require a large number of converters/inverters. Many new types of inverters have been created in recent decades, and these circuits will largely improve the power factor and increase the power efficiency for the future. This book covers advances DC/AC inverters that are both concise and useful for engineering students and practicing professionals. It uses 150 diagrams to introduce more than 100 topologies of the advanced inverters originally developed by the authors. The book includes more than 50 new circuits"--